ANALISIS KEBERLANJUTAN PERIKANAN TANGKAP DALAM PENGELOLAAN SUMBERDAYA PESISIR DAN LAUT YANG BERBASIS KEARIFAN LOKAL DI GAMPONG LAMBADA LHOK, KABUPATEN ACEH BESAR - Denny Yacob Yacob; Taqwaddin .; Chaliluddin . (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2016)
Management of coastal and marine resources in Aceh, especially in Gampong Lambada Lhok, Aceh Besar District recognizes the existence of local wisdom values in the community's sustainable life. This study aims to (1) document the values of local wisdom that is closely related to the management of coastal and marine resources in Gampong Lambada Lhok, Aceh Besar District, (2) analyze the sustainability of capture fisheries in the management of coastal and marine resources based on local wisdom in Gampong Lambada Lhok, Aceh Besar District. This research uses content analysis method (qualitative and cuantitative method) and RAPFISH method (survey method and study of literature), using questionnaire as data collecting tool. Respondents consist of: Panglima Laôt Aceh, Head of Marine and Fisheries Aceh Besar District, Panglima Laôt Aceh Besar District, Panglima Laôt Lhôk (each subdistrict), fisherman (handline and gillnet) boat owner, pawang and community motivator. The results show that (1) the local wisdom values contained in the management of coastal and marine resources in Gampong Lambada Lhok, Aceh Besar District are (a) the day of abstinence of meulaôt; (b) the existence of custom meulaôt; (c) the existence of social and economic customs of fisherman. (2) The sustainability of capture fisheries in the management of coastal and marine resources based on local wisdom in Gampong Lambada Lhok, Aceh Besar District shows; 5 (five) dimensions of sustainability (ecological, economic, social, technology and institutional dimensions) only 4 (four) dimensions are on the sustainability index, except for 1 (one) dimension ie technology that is in index less sustainability